Effectiveness of Giving Probiotics in Preventing Acute Diarrhea with A History of Recurrent Diarrhea - Ekayanti Ekayanti; Alliah Nuranggraeni; Rifatul Choirriyah; Risa Eriska (Indonesian Journal of Global Health Research, 2025)
One of the public health problems that occurs in infants and toddlers in Indonesia is diarrhea, and is one of the causes of death in toddlers. One of the efforts to prevent acute diarrhea with a history of recurrent diarrhea is therapy using probiotics. This study aims to determine the effectiveness of probiotic administration in treating diarrhea in toddlers with a history of recurrent diarrhea. The design of this study was a quasi-experiment with a non-randomized pre-test-post-test design, pretest and posttest in the intervention group (standard therapy and given probiotic therapy) and control group (standard therapy without probiotic therapy, analysis using t-paired test and independent test. Consecutive sampling technique, obtained 40 respondents (20 toddlers given probiotic therapy and 20 toddlers given standard therapy without probiotics). structured questionnaire instruments made by the researchers themselves and have been tested for validity (p < 0.05) and reliability (α = 0.961).